MOTIVES AND SATISFACTION OF INDONESIAN WOMEN IN WATCHING THAI SERIES “KINNPORSCHE THE SERIES” - Azzahra, Annisa Nursabrina; Esfandari, Diah Agung (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The internet does not only impact communicating media, but broadcast media is also affected by the emergence of internet-based broadcasting platforms. Through this platform, audiences can watch foreign shows with various genres, including the boys' love genre, such as KinnPorsche The Series, which comes from Thailand. This study aims to determine the motives and satisfaction of Indonesian female audiences in watching the boys' love series